The moderating effect of age in the relationship between e-government services and job performance [El efecto moderador de la edad en la relación entre los servicios de gobierno electrónico y el desempeño del trabajo] - Almashaqbeh K.M.; Ali K.B. (Universidad del Zulia, 2024)
Indexed by WOS/ Scopus